2012
DOI: 10.1002/cssc.201100481
|View full text |Cite
|
Sign up to set email alerts
|

Reduction of CO2 to CO at Low Overpotential in Neutral Aqueous Solution by a Ni(cyclam) Complex Attached to Poly(allylamine)

Abstract: Less is more: Nickel cyclam complexes are known as efficient catalysts for the electrochemical reduction of CO(2) to CO, despite having overvoltages of more than 0.6 V. Incorporating [Ni(cyclam)](2+) into poly(allylamine) through axial coordination of pyridine enables the electrochemical reduction of CO(2) to CO near the thermodynamic potential of -0.78 V (vs. Ag/AgCl) at pH 8 with a current efficiency of 90 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
23
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(24 citation statements)
references
References 23 publications
1
23
0
Order By: Relevance
“…An approach is based on the electrochemical reduction of CO 2 on metallic cathodes. Although this method requires a very negative potential, the use of a metal complex catalyst such as [Ni(cyclam)] 2 + [8] and its derivatives [9] was shown to allow the conversion of CO 2 into CO at a reasonable voltage [approximately -1.25 vs. saturated calomel electrode (SCE)]. However, some limitations remain, since at negative potentials the use of mercury electrodes is essential to optimize the selectivity of the process, by suppressing or, at least, minimizing, the competitive reduction of proton to hydrogen occurring at the electrode (recently, the use of a glassy carbon electrode has been proposed [10]).…”
Section: Introductionmentioning
confidence: 99%
“…An approach is based on the electrochemical reduction of CO 2 on metallic cathodes. Although this method requires a very negative potential, the use of a metal complex catalyst such as [Ni(cyclam)] 2 + [8] and its derivatives [9] was shown to allow the conversion of CO 2 into CO at a reasonable voltage [approximately -1.25 vs. saturated calomel electrode (SCE)]. However, some limitations remain, since at negative potentials the use of mercury electrodes is essential to optimize the selectivity of the process, by suppressing or, at least, minimizing, the competitive reduction of proton to hydrogen occurring at the electrode (recently, the use of a glassy carbon electrode has been proposed [10]).…”
Section: Introductionmentioning
confidence: 99%
“…1618 Although recent work has shown that immobilization of a cobalt porphyrin onto conducting diamond 19 or nickel cyclam onto a conducting poly(allylamine) support 20 can promote the electrocatalytic production of CO, these heterogeneous architectures do not currently display technologically relevant current densities (fast kinetics) for CO 2 conversion applications.…”
Section: Introductionmentioning
confidence: 99%
“…It has been previously established that histidine residues can be used to attach synthetic metal compounds to macromolecules, and [1] is known to bind pyridine, 22 which has similar electronic and geometric properties to imidazole. Wild-type (WT) azurin has a single, partially-exposed His residue at position 83 that is available for coordinating [1]; putative secondary sphere interactions around His83 are detailed in Figure S1.…”
mentioning
confidence: 99%